Substantial HbA1c Reduction Following Intermittent-Scanning Continuous Glucose Monitoring Was Not Associated With Early Worsening of Retinopathy in Type 1 Diabetes. (July 2022) - Linton, Kathryn; Stimson, Roland H.; Dover, Anna R.; Forbes, Shareen; Madill, Karen; Annoh, Roxanne; Strachan, Mark W. J.; McKnight, J. A.; Wright, Rohana J.; Gibb, Fraser W.
Background: Early worsening of diabetic retinopathy (EWDR) was observed in the intensively treated arm of the Diabetes Control and Complications Trial (DCCT) before long-term benefits accrued. We sought to assess whether there may be an increased risk of EWDR in high-risk individuals following intermittent-scanning continuous glucose monitoring (iscCGM) commencement. Methods: An observational study of 139 individuals with type 1 diabetes ≥5 years duration and with baseline HbA1c >75 mmol/mol (9.0%). This cohort was stratified by subsequent HbA1c response to iscCGM (best responders and non-responders). Pan-retinal photocoagulation (PRP), worsening retinopathy status and new development of retinopathy were compared between groups. Results: HbA1c change was -23 mmol/mol (IQR -32 to -19) (-2.1% [-2.9 to -1.8]) in responders and +6 mmol/mol (2-12) (+0.6 [0.2-1.1]) in non-responders ( P  < .001). There was no difference in subsequent PRP between responders (14.1%) and non-responders (10.3%, P  = .340). Baseline HbA1c (HR 1.052 per mmol/mol, P  = .002) but not response category (HR 1.244, P  = .664) was independently associated with the risk of requiring PRP. Worsening of retinopathy was not different between responders (16.9%) and non-responders (20.6%, P  = .577), and the same was true with respect to new development of retinopathy (33.3% vs 31.8%, P  = .919). Conclusions: In a cohort enriched for risk of diabetic retinopathy, reduction in HbA1c did not result in an increased risk of PRP, worsening retinopathy, or new development of retinopathy. These findings offer reassurance that substantial reduction in HbA1c is not independently associated with early worsening of diabetic eye disease in iscCGM users.